Challenges and principled responses to privacy protection from biometric technology in China - Zhang, Yi; Liao, Bohua; Lei, Ruipeng (Acta Bioethica, 2023)
Biometric technology has transformed human biological characteristics into a new form of privacy, and the misuse of this technology poses challenges to protecting this new privacy. This article initially defines biometric technology and biometric characteristics, further demonstrating why biometric characteristics belong to personal privacy and how biometric technology poses challenges to its protection. Through analysis, this article argues that the essence of these challenges is the conflicts between the ethical principle of privacy protection and the ethical principle of maximizing social benefits. In order to address these challenges, it is necessary first to weigh the fundamental ethical principles. The two basic principles of privacy protection and maximizing social benefits are not mutual antagonism but hierarchy, and this hierarchy should be based on the principle of practical feasibility. That is, applying biometric technology should first meet the principle of practical feasibility and, on this premise, realize the principle of maximizing social benefits based on not infringing on the principle of privacy protection.